Where can Tanzania health system integrate clinical management of patients with dual tuberculosis and diabetes mellitus? A cross-sectional survey at varying levels of health facilities - Nyasatu G. Chamba; Kenneth C. Byashalira; PendoMartha J. Shayo; Kaushik L. Ramaiya; Rachel N. Manongi; Peter Daud; Blandina T. Mmbaga; Nyanda E. Ntinginya; Troels Lillebæk; Ib C. Bygbjerg; Dirk L. Christensen; Stellah G. Mpagama (Elsevier, 2022)
Objective: To assess the current Tanzania health facilities readiness in integrating clinical management of dual Tuberculosis (TB) and Diabetes Mellitus (DM) by using the Service Availability and Readiness Assessment (SARA) manual of the World Health Organization prior to implementing an integrated service model. Study design: Cross-sectional study. Methods: A needs assessment survey was conducted at varying levels of health care facilities. The SARA manual evaluated the service delivery outcomes in terms of availability of guidelines, medicines and diagnostic equipment, training of healthcare workers in providing TB and DM care, and patient record review. Data were analyzed using Statistical Package for Social Science version 26. Results: Among 29 health facilities selected, three were regional referral hospitals, eight were district hospitals and eighteen were health centers. Baseline investigations revealed that GeneXpert MTB/RIF machines were present in 10 (34.5%) facilities, and glycated hemoglobin devices were present in two (6.9%) facilities, while all health facilities had a glucometer. The presence of an attending medical doctor in 19 (65.5%) facilities and the presence of operating biochemistry analyzers in 15 (51.7%) facilities were two mandatory variables used to assess readiness. Among the various guidelines observed, none of the facilities had the 2016 DM guidelines. Overall, 15 (51.7%) health facilities were ready to integrate dual TB and DM services. Conclusion: Integrative TB/DM screening and management activities can be achieved only if integration initiatives are prioritized at all levels of health facilities and among health policy makers in Tanzania. At least half of the health facilities were prepared to integrate the management of dual TB/DM. However, there is an urgent need to mobilize significant resources to improve the integration in these facilities, such as management guidelines and diagnostics..